Effect of using a high performance-low pollution muffler (hplpm) with catalytic converter on fuel consumtion and performance of 110cc - Susanto, Nugroho Fajar; Roziqin, Ahmad; Naryanto, Rizqi Fitri; Mujaki, Ahmad (Universitas Negeri Semarang, 2024)
The increse in the number of motorcycles to fulfil mobility is domianted by matic type. Over time the vehicle will experience a derease in performance and appearance, triggering modification. the purpose of this study was to determine the difference in motorcycle performance with the use of standard exhaust, HPLPM 2 + catalytic converter and HPLPM mod + catalytic converter. This reaserch was conducted with a quantitative research meode with an experiemental approach, performance testing test data at engine speed of 3000-9000 rpm. Engine temperature 80 degree with pertamax fuel ocatane 92. In this study, HPLPM mod + catalytic converter produces 12,23 N.m of torque at 4500 rpm, the highest power produced by HPLPM 2 + catalytic converter 8,27 Hp at 5500 rpm. exhaust HPLPM mod + catalytic converter is able to maintain power at high rpm 7,70 Hp at 8250 rpm.